Signatures of galactic magnetic lensing upon ultra high energy cosmic rays - Harari, Diego (2000)
We analyse several implications of lensing by the regular component of the galactic magnetic field upon the observed properties of ultra high energy cosmic rays. Magnetic fields deflect cosmic ray trajectories, causing flux (de)magnification, formation of multiple images of a single source, and time delays. We derive the energy dependence of these effects near the caustics at which the flux amplification of a point source diverges. We show that the large magnification of images around caustics leads to an amplification bias, which can make them dominate the flux in some energy ranges. We argue that clustering in the arrival directions of UHECRs of comparable energy may be due to magnetic lensing around caustics. We show that magnetic lensing can also significantly alter the observed composition of cosmic rays at the highest energies. We also show that the time delay between events from a single image may monotonically decrease with decreasing energy in the neighborhood of a caustic, opposite to its behaviour in normal regions. Lensing effects in the magnetic field model considered are significant for cosmic rays with ratio between energy and electric charge E/Z between 10¹⁸ and 5 10¹⁹ eV approximately. Similar effects may also occur for higher E/Z values if the galactic magnetic field is stronger or more extended than what is assumed here, or in the magnetic field of source galaxies, or even in intergalactic fields.